Men and Nations - Halle, Louis Joseph (Princeton, NJ : Princeton University Press, 2015)
Men and Nations is the fruit of one man's extended effort to solve the philosophical problems that underlie the practical dilemmas of human society. This undertaking began when, as an adviser in the U.S. State Department, Mr. Halle found himself groping for the deeper explanation of political problems that could not be understood within the limits of the terms in which they presented themselves, The philosophical system that resulted is proposed here as a basis for the understanding and teaching of politics. It is, however, a complete philosophy of life, not limited to politics. Men and Nations represents an effort to resume progress in the great tradition of political philosophy, to present a foundation for the continued progress of our societies.Originally published in 1962.The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These editions preserve the original texts of these important books while presenting them in durable paperback and hardcover editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905.
Frontmatter -- Preface -- Contents -- Part One: The Text -- Chapter I. The Dual Philosophy -- Chapter II. The Philosophy and The Community -- Chapter III. The Philosophy, The Community, and The State -- Chapter IV. The Locus of Respons -- Chapter V. The Validity of Ideas -- Chapter VI. Progressive Revelation -- Chapter VII. The Organization of Mankind -- Part Two: Amplifications -- Index
Mode of access: Internet via World Wide Web.
In English.
Description based on online resource; title from PDF title page (publisher's Web site, viewed 08. Jul 2019)
Keywords: Political science; PHILOSOPHY / Political